How to preserve the Minangkabau Traditional Village study case : Jorong Balerong Bunta, Nagari Rao-rao, Tanah Datar, West Sumatera / Desy Aryanti, Othman Mohd Nor and Zulkefle Hj Ayob - Aryanti, Desy; Mohd Nor, Othman; Ayob, Zulkefle (2012)
Minangkabau is one of a huge ethnic group in Indonesia, which famous for its matrilineal system, high well-developed cultures and entrepreneurships. Its traditional and customhouses, known as “Rumah Gadang or Rumah Bagonjong”, are exceptionally renowned and to be proud of. At present, the existence of minangkabau‟s customhouses are severely threatened and being thrust aside due to peoples current interests on concrete construction. Many are now not maintain, in poor conditions, dilapidated with mold and leakages; while many others have been altered and attached with concrete construction. Since long ago, the Minangkabau region has enthralled many locals as well as foreign researchers due to its unique culture and historic value. The attention extended to the Rao – Rao‟s region as established in the history and “Tambo Alam Minangkabau”, which was the earliest minangkabau‟s origin settlement migrated from Pariangan, Padang Panjang. Therefore, this incite further debate among scholers from various knowledge major and thus inspire this research on the region. The method of research includes field survey for data collection, mapping process, identification of supporting factors as well as conducting in person interviews with local citizens. Additional datas were attained from Bung Hatta Universities by tof their recurrent „On Site Study‟ (Kuliah Kerja Lapangan) in Rao –Rao region. Based from the research findings, maps are being generated for each area (jorong) in Rao –Rao region and are still in it preliminary stage. Eventhough there are dilapidated and unmaintained traditional houses, there are still many original Minangkabau villages full with its traditional houses in existence and are in good condition. Therefore, a heritage trail is being designed to promote Rao – Rao region as a Historic Tourism centre and visitors will be able to see the Minangkabau traditional houses in its original village setting. This is evident at only Jorong Balerong Bunta with it ‘Rumah Gadang Sembilan Ruang’. It is unfortunate after the 1926 great fire in Rao - Rao most of these ‘Rumah Gadang Sembilan Ruang’ in other Jorong were not treated nor being rebuilt